1973
DOI: 10.1159/000180234
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Terminal Renal Failure in Diabetic Patients by Regular Dialysis Therapy

Abstract: Ten diabetics, nine requiring insulin, were kept alive on peritoneal dialysis and haemodialysis for varying periods of time, with a mean suvival rate of 7 months only per patient. The management of the cardiovascular problems affecting the brain, eye, heart, and peripheral vessels far exceeded the difficulties in managing their diabetic state. Two patients were maintained on home dialysis, one with full sight, the other with partial sight. One patient received a combined renal and pancreatic transplant and req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 2 publications
(2 reference statements)
2
19
0
1
Order By: Relevance
“…Reports of hemodialysis for diabetic nephropathy have been most dis appointing [138], Only 8 of 39 patients survived as long as 3 months in the series of C h a z a n et al [19], while 78% of the patients treated by G havam ian et al [48] had died within 1 year. Serious difficulties with hypoglycemia, clotted shunts, infection, congestive heart failure and muscle wasting occurred.…”
Section: Late Abnormalitiesmentioning
confidence: 99%
“…Reports of hemodialysis for diabetic nephropathy have been most dis appointing [138], Only 8 of 39 patients survived as long as 3 months in the series of C h a z a n et al [19], while 78% of the patients treated by G havam ian et al [48] had died within 1 year. Serious difficulties with hypoglycemia, clotted shunts, infection, congestive heart failure and muscle wasting occurred.…”
Section: Late Abnormalitiesmentioning
confidence: 99%
“…Of 340 patients in whom visual status was given, 111 (32.6%) had deterio ration of vision [3,4,[6][7][8]10,12,13,16,17,19]. There are no progressive studies to indicate the factors responsible for decrease in visual acuity, though the effect of heparin on the known tendency of diabetics to develop retinal hemorrhage is suspect.…”
Section: Maintenance Hemodialysismentioning
confidence: 99%
“…A total of 96 out of 501 patients (19.2%) developed either myocardial infarcts or con gestive heart failure while undergoing MD [4,6,8,11,15,19,21]. A third manifestation of diabetic vasculopathy, cerebrovascular hem orrhage, or thrombosis was noted in about 1 in lOhemodialyzed diabetics [4,6,8,11,15,21].…”
Section: Maintenance Hemodialysismentioning
confidence: 99%
“…Although other authors have suggested larger doses of intraperitoneal insulin with or without subcutaneous insulin, or subcutane ous insulin alone [16,17], in our experience the intraperitoneal dosage schedule, as de scribed, is very satisfactory. It is essential to take precautions to prevent post-dialysis hypoglycemia by omitting insulin from the last 4 exchanges when using the cycler or manual method of dialysis, or by adding glucose to the peritoneal cavity at the end of dialysis when the PDS machine is used.…”
Section: Discussionmentioning
confidence: 56%